Donor organizations and technical assistance programs : a guide to who is supporting sustainable resource development in the Eastern Caribbean - Towle, Judith A. (Island Resources Foundation St. ThomasVG, 1995)
Presents an alphabetized list by the name of the organization. Includes donor and assistance groups whose programs have some bearing on the English-speaking Eastern Caribbean.